Odpowiedź :
a)
[tex] \frac{ {a}^{6} \times {a}^{3}}{ {a}^{5} \times {a}^{2} } = \frac{ {a}^{9} }{ {a}^{7} } = {a}^{9} \div {a}^{7} = {a}^{2} [/tex]
b)
[tex] \frac{ {x}^{9} \div {x}^{3} }{ {x}^{5} \times {x}^{2} } = \frac{ {x}^{6} }{ {x}^{7} } = {x}^{6} \div {x}^{7} = {x}^{ - 1} [/tex]
c)
[tex] \frac{ {b}^{ - 3} \times {b}^{8} }{ {b}^{4} } = \frac{{b}^{5} }{ {b}^{4} } = {b}^{1} = b [/tex]
d)
[tex] \frac{ {( {x}^{4} )}^{ - 3} \times {x}^{5} }{ {x}^{5} } = \frac{{x}^{ - 12} \times {x}^{5} }{ {x}^{5} } = \frac{ {x}^{ - 7} }{ {x}^{5} } = {x}^{ - 7} \div {x}^{5} = {x}^{ - 12} [/tex]
Mam nadzieję że dobrze